The Effect of Mass, Depth, and Properties of the Soil Below the Raft Foundation on the Seismic Performance of R.C. Plane Frames - Alomari, J. A. (Engineering, Technology & Applied Science Research, 2019)
Soil structure interaction has been the subject of numerous studies. The foundation soil has a definite effect on the performance of structures during seismic excitation. Recent studies show that the effect of soil-structure interaction SSI may be detrimental to the structure during seismic excitation. In this study, the effect of consideration of the soil below foundation and its depth, and the soil modulus of elasticity on the response of structures is investigated. The number of mode shapes considered has an effect on the accuracy of the values of structure response. A structural model consisting of an 8-story reinforced concrete frame resting on raft foundation, and including the soil below the raft is analyzed. The frame is analyzed using SAP2000 software, and time history and modal analysis are carried out with varying values of both soil depth and soil modulus of elasticity. The soil below the foundation is connected to the raft elements by gap links. Gap element links are compression–only members with appropriate stiffness, which are active only in compression. Modal analysis results show that the periods of vibration decrease as the modulus of elasticity of the soil increases. Periods of vibration of the frame without the soil mass consideration are less than those when the soil mass below the raft is considered, and they increase with increased depth of foundation to a certain limit. The structures response in the form of columns shear forces and story displacements are also evaluated under the variable parameters considered.